The Role Of Organizational Culture In Enhancing Teacher Leadership In Schools: A Literature Review - Monigir, Non Norma; Samuel H. Mosey; Meytha M. Wongkar; Davison Pagawak (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2024)
This article aims to examine the role of organizational culture in improving teacher leadership in schools. A supportive and healthy organizational culture can facilitate teacher leadership development, increase collaboration between teachers, and encourage teachers to innovate in the learning process. This study draws on a literature review from various relevant journals between 2020 and 2023, as well as identifying supporting and inhibiting factors in teacher leadership development. The results of the study show that an organizational culture based on cooperation, effective communication, and appreciation for teacher professionalism can strengthen the role of teacher leadership in schools. Support from democratic principals and providing opportunities for teachers to participate in decision-making also proved important in improving teacher leadership. However, inhibiting factors such as limited resources and resistance to change are challenges that must be overcome to improve the effectiveness of teacher leadership. These findings suggest that schools need to create a positive organizational culture, provide adequate resources, and provide the necessary support for teacher leadership development.